DEVELOPMENT OF MULTICHANNEL DYNAMIC SIGNAL ANALYZER SOFTWARE USING DAQCARD 6024E DATA ACQUISITION CARD - HENDRA WARDHANA (NIM : 13105103); Pembimbing : Dr. Ir. Zainal Abidin, ANGGA
Dynamics laboratory of ITB has developed several data acquisition devices for vibration measurement. The data acquisition devices however often find some problems during measurement due to noise signal or power line leakage. An alternative way to overcome this problem is to use a dynamic signal analyzer hardware which work based on a portable computer or laptop. This dynamic signal analyzer hardware needs software to control its operation. In this research, multichannel dynamic signal analyzer software has been developed successfully. The multichannel dynamic signal analyzer software is based on laptop and used to control DAQcard 602E data acquisition card (PCMCIA). This software is developed based on LabVIEW 8.5 graphical programming language. This software is able to acquire signals from 16 channel analog inputs. This software can process and display result in form of linear spectrum, spectral map, or order tracking. In addition, this software comes with data logger capability, graph of vibration level trending, and auto range capability. To gather information about the performance of the hardware and software, a calibration and tests has been done. Based on the results of calibration and tests, it can be concluded that the developed software is able to operate properly. The occurrence of measurement data reading error is caused by unavailability of an anti-aliasing filter, low sampling frequency or noise signal. To overcome the unavailability of an anti-aliasing filter, the sampling frequency must be increased. Reliability test results show that the software can acquire and store data consistently for nearly 20 hours.